Age-Based Incidence of Dens Fracture Has Unimodal Distribution Rather Than Commonly Claimed Bimodal Distribution - Rita Somogyi, BA; Spencer Smith, BS; Jonathan Kark, MD; Won Hyung A. Ryu, MD; Jung Yoo, MD (JBJS Open Access, 2024)
Background:. Type-II dens fractures have long been described in the literature as occurring in a bimodal distribution, peaking in young adulthood as well as in older adulthood; however, the origin of this claim is unclear. The primary goal of this study was to examine the incidence of type-II dens fractures and assess for bimodality. Methods:. This is a retrospective cross-sectional review of the National Trauma Data Bank (NTDB) records on traumatic type-II dens fractures between October 2015 and December 2016. Rates were obtained from the NTDB, and the incidence per 100,000 was ascertained by utilizing U.S. Census data from 2016. Subgroupings by gender and Black or White race were also examined. Results:. Dens fractures occur unimodally, peaking around 89 years of age overall, skewed left by high rates in older White adults. The Black subgroup demonstrated trimodality, with the fracture incidence peaking at 25, 62, and 82 years of age. Rates among Black and White patients were similar until age 65, after which dens fractures occurred disproportionately in White patients. Fractures prior to age 75 occurred predominantly in men. Conclusions:. The evidence derived in this study challenges the common belief that type-II dens fractures occur bimodally across the entire population. However, there remains utility in considering younger and older patients as distinct groups for the purposes of management.